2010
DOI: 10.3390/molecules15031668
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Antibacterial, Antifungal and Antioxidant Activity and Total Content of Phenolic Compounds of Cell Cultures and Wild Plants of Three Endemic Species of Ephedra

Abstract: Investigations were carried out to determine antimicrobial and antioxidant properties and total phenol content of three wild species of Ephedra compared with their respective callus cultures. Callus induction was performed in a standard Murashige and Skoog (MS) medium with the following hormonal ranges (mg/L) for every species NAA:1.5, Kin:1 for Ephedra strobiliacea, NAA:2, Kin:1 for Ephedra procera and NAA:2, Kin:0.5 for Ephedra pachyclada. These ranges of PGPR (Plant Growth Promote Regulators) were chosen ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 26 publications
4
45
2
Order By: Relevance
“…In the past few years, several effects of Ephedra pachyclada extract on different bacteria have been reported. In 2010, Parsaismehr and his colleagues studied antibacterial effects of three species of Ephedra on Gram negative bacteria and unexpectedly observed that the most antimicrobial effect of these plant was on Pseudomonas aeruginosa, which corresponded with the results of the current study [15]. In 2009, Chi-hoon lee and colleagues examined antimicrobial effect of the Ephedra pachyclada plant on some intestinal bacteria, and observed that Ephedra pachyclada has antibacterial effect on some intestinal bacteria at 1 mg/mL concentration [19].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In the past few years, several effects of Ephedra pachyclada extract on different bacteria have been reported. In 2010, Parsaismehr and his colleagues studied antibacterial effects of three species of Ephedra on Gram negative bacteria and unexpectedly observed that the most antimicrobial effect of these plant was on Pseudomonas aeruginosa, which corresponded with the results of the current study [15]. In 2009, Chi-hoon lee and colleagues examined antimicrobial effect of the Ephedra pachyclada plant on some intestinal bacteria, and observed that Ephedra pachyclada has antibacterial effect on some intestinal bacteria at 1 mg/mL concentration [19].…”
Section: Discussionsupporting
confidence: 62%
“…In Ephedra pachyclada plant; phenolic compounds have a crucial role in inhibitory activity of the hydroxyl groups on free radicals. Therefore, these phenolic compounds may be in direct relation with antioxidant activity of flavonoids and phenylpropanoids biosynthesis [15]. Also, several studies examined antimicrobial effects of Ephedra pachyclada plant on microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are found in the region of Iran, northwest India, and Pakistan (Balochistan). These shrub plants also showed antioxidant and antimicrobial activities (13)(14)(15). Ephedra basic compounds consist of the alkaloids E and PE and phenols (16).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro cultures have the potential to form secondary metabolites and to exhibit bioactivity comparable to the original plant [4,5]. Cultured cells may serve industrial purposes, e.g.…”
Section: Introductionmentioning
confidence: 99%